Infection with Classical Swine Fever Virus Induces Expression of Type III Interferons and Activates Innate Immune Signaling - Cai, Binxiang; Bai, Qingling; Chi, Xiaojuan; Goraya, Mohsan U.; Wang, Long; Wang, Song; Chen, Biao; Chen, Ji-Long (Frontiers in Microbiology, 2017)
Classical swine fever virus (CSFV) commonly infects the lymphatic tissues and immune cells of pigs and could cause a lethal disease in the animals. The process and release of cytokines like type III interferon (IFN) is one of the important responses of the host innate immunity to viral infection. However, little information is available about type III IFNs response to the CSFV infection. In this study, we investigated the expression of type III IFNs including interleukin-28B (IL-28B) and IL-29 in PK-15 cells and pigs following CSFV infection. We found that infection with CSFV was able to induce expression of IL-28B and IL-29 in PK-15 cells, although the increased levels of type III IFNs were limited. Importantly, up-regulation of IL-28B and IL-29 was further observed in CSFV infected animal tissues. The production of IL-28B and IL-29 was reduced by the inactivation of NF-B in cells, indicating that activated NF-B is required for efficient expression of type III IFNs induced by CSFV. Moreover, our experiments demonstrated that infection with CSFV strongly stimulated the downstream of STAT1 signaling in vitro and in vivo. In addition, several critical IFN-stimulated genes (ISGs) including IFITM3, OASL, OAS1 and ISG15 were significantly upregulated at both mRNA and protein levels in PK-15 cells and infected pigs. Together, these results reveal that CSFV can trigger host antiviral immune responses including production of type III IFNs, activation of STAT1, and induction of some critical ISGs.